The antecedents of political capabilities: A study of ownership, cross-border activity and organization at legacy airlines in a deregulatory context - Lawton, Thomas; Rajwani, Tazeeb; Doh, Jonathan (Elsevier Science B.V., Amsterdam., 2013)
Governments and ownership structures can both facilitate and constrain organizational value creation. Firm-level political strategy is a frequent response to protect or promote organizational interests. When effectively configured and implemented, these political strategies can become capabilities. This inductive study examines the antecedents of political capabilities in European airlines within the context of cross-border market deregulation. Our central contribution is an understanding of how management teams from non-state and state airlines organize and develop divergent corporate political capabilities in this context. While managers' actions in response to specific public policy processes can create political capabilities, the outcome is moderated by the nature of corporate ownership and the relative influence of public and private stakeholders on capability formation. Our theoretical contribution is to extend the study of organizational capabilities into the non-market context through analyzing how European flag carrier airlines organized their political capabilities in anticipation of a changing transnational policy context.
Keywords: Corporate political activity, organizational capabilities, ownership, air transport, cross-border deregulation